2011
DOI: 10.1007/s00360-011-0552-8
|View full text |Cite
|
Sign up to set email alerts
|

A thermal hysteresis-producing xylomannan glycolipid antifreeze associated with cold tolerance is found in diverse taxa

Abstract: The presence of large-molecular-mass, thermal hysteresis (TH)-producing antifreezes (e.g., antifreeze proteins) has been reported in numerous and diverse taxa, including representative species of fish, arthropods, plants, fungi, and bacteria. However, relatively few of these antifreeze molecules have been chemically characterized. We screened diverse species by subjecting their homogenates to ice-affinity purification and discovered the presence of a newly identified class of antifreeze, a xylomannan-based TH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 42 publications
0
41
0
Order By: Relevance
“…Research about the mechanism of ice initiation in plants has greatly decreased recently because of its essential role in specific aspects of cold hardiness (Gusta et al 2009;Aryal & Neuner 2010;Hacker et al 2011;Walters Jr et al 2011). Ice formation may take place either in the intracellular or extracellular spaces depending on the cooling conditions (Guy 1990).…”
Section: Low-temperature Stress (Frost Damage)mentioning
confidence: 99%
“…Research about the mechanism of ice initiation in plants has greatly decreased recently because of its essential role in specific aspects of cold hardiness (Gusta et al 2009;Aryal & Neuner 2010;Hacker et al 2011;Walters Jr et al 2011). Ice formation may take place either in the intracellular or extracellular spaces depending on the cooling conditions (Guy 1990).…”
Section: Low-temperature Stress (Frost Damage)mentioning
confidence: 99%
“…In response to decreasing temperature and reduced photoperiod in the autumn, D. canadensis cease feeding and drinking, clear gut contents and synthesize AFPs, as well as antifreeze glycolipids and glycerol (Olsen and Duman, 1997;Duman et al, 2010;Walters et al, 2011). During warm periods in the winter and in early spring when snowmelt occurs, the larvae appear to drink, but this has not been conclusively demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Antifreeze proteins and glycoproteins are perhaps the most celebrated of the molecules associated with low-temperature tolerance and have been well-characterised in insects (Doucet et al, 2009;Duman, 2015;Bar Dolev et al, 2016). Recently, a xylomannan glycolipid with activity similar to that of well-known antifreeze proteins was identified in a freeze-tolerant Alaskan beetle (Walters et al, 2009); these glycolipid antifreeze proteins have subsequently been found in a range of overwintering insects (Walters et al, 2011). These glycolipids consist of a repeated xylose-mannose backbone with fatty acyl moieties attached (Fig.…”
Section: Unusual Lipids and Lipid Derivativesmentioning
confidence: 99%